Differences for employees who use BIM/VDC in the construction workplace - Inguva, Girija, author; Clevenger, Caroline, advisor; Ozbek, Mehmet, committee member; Atadero, Rebecca, committee member (Colorado State University. Libraries, 2014)
There is growing recognition across the US construction industry for the benefits of organizational adoption of Building Information Modeling, also referred to as Virtual Design and Construction (BIM/VDC). One of the key factors that enables successful organizational adoption of new technologies is the adoption of these technologies by key participants, in this case by BIM employees. Their positive experiences at their current organization determine their continuation on a BIM/VDC path, thus leading to consistent organizational adoption and negative experiences could mean that they migrate from a BIM career to a Non-BIM career or to another organization to seek better experiences. This research aims to study the perceptions of BIM employees as compared to the perceptions of Non-BIM employees in the construction industry in four key categories: work life balance, career advancement, workplace experience and skill levels. An online survey is used and responses are compared first using averages and then using Pearson's X2 or Fisher's probability test to test for statistical significance where applicable. Differences inform us of the advantages or challenges of a BIM/VDC career at an individual level. Additionally, differences between men and women are also studied, along with differences between BIM employees from organizations with a separate BIM/VDC department and BIM employees from organizations without a separate BIM/VDC department. The general trends observed in terms of averages indicate that BIM/VDC personnel are generally more satisfied with their jobs and consider common barriers to career advancement to be of lesser relevance than their Non-BIM counterparts. The fact that most differences are not statistically different also suggests that BIM employees may not be treated that differently from Non-BIM employees. Of all groups, the most positive perceptions are reported by male BIM respondents from organizations without separate BIM/VDC departments.
Keywords: BIM; VDC; employee perceptions; construction management; building information modeling